The Effect of Phytoestrogens in Feed on Ovarian Activity and Fertilization Indicators in Animals - Suhrob, Aminov (American Journal of Biology and Natural Sciences, 2025)
The article discusses the effect of phytoestrogens in feed on ovarian activity and fertilization indicators in animals. It is noted that when used in moderate amounts, phytoestrogens can stimulate follicular development and improve fertilization efficiency. However, in excessive quantities they disrupt hormonal balance and reduce reproductive performance. In addition, the possibilities of using phytoestrogen-rich plants in animal husbandry are analyzed.